Eukaryotic Microalgae and Cyanobacterial Diversity Analysis from Bharathidasan University Campus, Tamil Nadu, India: Life Sciences-Phycology - S, Soundararajan; R, Karkuvelraja; Prasad S, Sanjay; Chitthan S, Vishnu; N, Thajuddin (International Journal of Life Science and Pharma Research, 2022)
Eukaryotic microalgae and Cyanobacteria have immense biodiversity, and are an almost unexploited resource. They have been identified as a hopeful and commercially valuable resource of high-value products such as proteins, fatty acids, pigments, vitamins, alkaloids, flavonoids and steroids etc., in the food and aquaculture industries. Microalgae are a promising candidate for the production of useful products due to their low cost biomass production, ease of cultivation, and glycosylation patterns similar to that of higher plants. Though quite a few species of microalgae have been identified as a potential candidate to fulfill our needs, remain unexplored. The aim of the present study is to enumerate the microalgal diversity in the vicinity of Bharathidasan university (Tiruchirapalli, TamilNadu, India). Physicochemical parameters of the water samples were also determined.the pH of the sites varied from 6.5 to 7.4, lkalinity was between 24 mg L-1 and 42 mg L-1, total alkalinity was between 312 mg L-1 and 681 mg L-1, calcium, magnesium, chloride and nitrate levels varied between 329 mg L-1and 1318 mg L-1, 220 mg L-1 and 826 mg L-1, 12.99 mg L-1 and 193.33 mg L-1, 4.0 mg L-1 and 9.8 mg L-1, respectively. Nitrite, total phosphorus and inorganic phosphorus levels were found to be between 2.1 mg L-1 and 4.3 mg L-1, 2.4 mg L-1 and 6.7 mg L-1, and 1.2 mg L-1 and 4.3 mg L-1. Biodiversity of both eukaryotic microalgae and cyanobacteria recorded the members of the belonging to Oscillatoria sp. are predominant in diversity and distribution followed by other taxa such as Spirulina laxissima, Staurastrum manfeldtii, Merismopedia elegans, Cosmarium blyttii and Cosmarium subcucumis.